Methods of Assess the Impact of Technological Variables Complex Spatial-Distributed Systems on Costs - Korneev A.M.; Shmyrin A.M.; Lavrukhina T.V.; Abdullakh L.S. (International Journal of Advances in Applied Sciences, 2016)
The paper considers the method of calculating costs, taking into account the effect of technological parameters; the model of forecasting of costs of production resources based on the matrix of costs are described; the methods of assess the impact of parameters of complex spatial-distributed systems on costs are presented.